Non-invasive Ventilation Treatment in a Patient with Severe Asthma Induced by Acute Cardiogenic Pulmonary Edema: Case Report (Annals of Medical Research, 2021)
None
Keywords: Asthma; Acute Cardiogenic Pulmonary Edema; Non-invasive Mechanical Ventilation.